Municipal internal control and monitoring of notifications issued by external control organizations: A case study in the CGM - Lucas, Airton Douglas de Andrade; Cristiane; Feitosa Cavalcante de Andrade Feitosa, Sarah; Santos , Sandra Maria dos (Contextus - Revista Contemporânea de Economia e Gestão, 2022)
The research analyzed how the internal control of the Municipality of Fortaleza monitors the notifications sent by the external control bodies to the various bodies of the Municipal Public Administration. For this purpose, a qualitative, descriptive research was used. The case study method is used, and secondary and primary data are used. It was concluded that the analyzed mechanism consists of an important internal control tool, which seeks to avoid the congestion of notifications coming from the external control institutions, serving as an aid in the adequacy of the answers to be forwarded.